Should you outsource analytics? - Fogarty, David; Bell, Peter C., 1944- (MIT, 2014)
The surge of interest in big data has led to growing demand for analytics teams. Assembling such teams, however, is difficult. For one thing, many companies lack the in-house knowledge and experience needed to put together a world-class analytics team. What's more, the labor market for analytics professionals has grown increasingly tight. The shortage of analysts — particularly those capable of developing and leading world-class teams that can enable a company to create a competitive advantage from its data and analytics — is driving organizations to consider outsourcing their analytics activities. Analytics is the latest in a string of activities companies are outsourcing to business process organizations (BPOs). It draws heavily on mathematics and statistics knowledge, and many analytics-oriented BPOs have operations in India. Although some companies have world-class analytics capabilities in-house, the authors posed the question: Can an analytically naïve company “buy” world-class analytics functions by hiring outside experts? The authors studied both four multinational companies that used one or more offshore analytics BPOs and four analytics BPOs. Two of the client companies had skills that were judged to be “analytically superior”; the other two were judged to be “analytically challenged.” The analytically challenged companies saw analytics BPOs as a way to obtain the resources and training needed to manage and execute their analytics and to gain quick access to important insights. By contrast, the analytically superior companies wanted to expand their internal analytic capabilities, in part because they wanted to preserve their ability to develop and protect intellectual property; they tended to use offshore BPOs to perform low-level analytics. According to the authors, the best analytics BPOs have core competencies that go beyond what most companies can perform on their own with internal teams. They advise companies working with analytics BPOs to be clear about who does what, who owns what, how each party can use the information it has and what happens to the information and knowledge in the event that the BPO is acquired.